Morphological evolution during partial re-melting of AISI D2 cold-work tool steel - Mohammed, M.N.; Omar, M.Z.; Syarif, J.; Salleh, M.S. (Universiti Kebangsaan Malaysia, 2014)
The impact of isothermal temperature and holding time on the microstructural evolution process is studied. This process is used to produce globular microstructures during partial re-melting of AISI D2 cold work tool steel. The experimental results showed that the optimum process factors should be selected according to the criteria for average grain size and shape factor and also by acknowledging the distribution of the liquid phase around the grains. With increasing isothermal temperature and holding time, the liquid phase starts to diffuse into the grain boundaries and spread more evenly. Also, the equiaxed grains were transformed into near-globular shape, which makes the grain size and shape factor more favourable for thixoforming. The work shows that the optimal process condition for the thixoforming of AISI D2 is 1340°C and 5-min holding time, having a shape factor of 1.13 and a particle size of 51 μm.